Thống kê khoa học và công nghệ phục vụ quản lý khoa học và công nghệ - Ban Biên tập (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Highlights the necessity, legal basis and role of S&T Statistical work; indicates clearly object, scope and content of Vietnam S&T Statistics; mentions entanglements to be settled in organizing S&T Statistics in provinces and cities today.